Hygiene dan Sanitasi Pengolahan Roti pada Pabrik Roti Paten Bakery - Fajriansyah Fajriansyah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Food is one of the principal ingredients in the framework of the growth and life of the nation and has an important role in national development. Control of factors premises, equipment, people and food enabling poor health disorders or food poisoning. The research method is descriptive with samples of food processing power as many as seven (7) people. The data collection conducted interviews using a questionnaire and checklist. Data analysis was performed manually and presented into a frequency distribution table. The results were obtained personal hygiene qualified only by 43,0%, processing methods eligible is still low (29,0%). Sanitation equipment is generally eligible (86,0%), and sanitary processing sites still little qualified (29,0%). Additionally, hygienic way of packaging is good is qualified by 86%. The conclusion shows that there are many circumstances in patent bakery bread factory production is still less qualified. Suggested to the factory owner in order to provide training to employees to further hone their knowledge in order to create quality bread eligible. Keywords: Hygiene, sanitation, and processing of bread